2006
DOI: 10.1161/01.str.0000195130.16843.ac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatosensory Stimulation on Use-Dependent Plasticity in Chronic Stroke

Abstract: Background and Purpose-There is a need to develop strategies to enhance the beneficial effects of motor training, including use-dependent plasticity (UDP), in neurorehabilitation. Peripheral nerve stimulation (PNS) modulates motor cortical excitability in healthy humans and could influence training effects in stroke patients. Methods-We compared the ability of PNS applied to the (1) arm, (2) leg, and (3) idle time to influence training effects in the paretic hand in 7 chronic stroke patients. The end point mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 12 publications
5
90
0
2
Order By: Relevance
“…19,20 This relative inability of 30 minutes training to elicit the desired effect on motor memory formation represents an excellent model against which to compare various strategies designed to boost training effects. It has been shown that dopaminergic agents could enhance training effects on motor memory formation in older adults 21 and in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This relative inability of 30 minutes training to elicit the desired effect on motor memory formation represents an excellent model against which to compare various strategies designed to boost training effects. It has been shown that dopaminergic agents could enhance training effects on motor memory formation in older adults 21 and in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of experiments, 2 hours of sensory stimulation increased the degree of plasticity. 21 The most extensively studied sensorystimulating drug by far is dextro-amphetamine. 22 In chronic stroke patients after 30 minutes of training, there was an increase not only in training-dependent plasticity but also in acceleration in the development of training-dependent plasticity when dextro-amphetamine was administered.…”
Section: Learning That Is Relevant To Recoverymentioning
confidence: 99%
“…8,9 During performance of motor tasks, repetitive activation of sensory input enhances motor cortical plasticity, establishing a mechanism for the role of sensory input in motor skill acquisition. [10][11][12] A sensory-based intervention called peripheral nerve stimulation (PNS) has been shown to increase motor cortical excitability and enhance outcomes of motor training after stroke. In a study of 22 subjects <6 months after stroke, PNS paired with 1 week of intensive task-oriented UE training was associated with more significant improvement in movement function than the effects of training alone as measured by the Wolf Motor Function Test (WMFT).…”
mentioning
confidence: 99%
“…In a study of 22 subjects <6 months after stroke, PNS paired with 1 week of intensive task-oriented UE training was associated with more significant improvement in movement function than the effects of training alone as measured by the Wolf Motor Function Test (WMFT). 13 A separate study by Sawaki et al 12 investigated the effects of PNS on voluntary movement of paretic thumb in 7 subjects at least 6 months post stroke. Significantly more neuroplastic change was associated with active PNS compared with sham conditions.…”
mentioning
confidence: 99%